2017
DOI: 10.1002/ar.23608
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Variations in the Soft‐Hard Tissue Junction of the Human Anterior Cruciate Ligament

Abstract: The role of the sub-bundles in the anterior cruciate ligament (ACL) has been defined, such that the anterior-medial bundle directly resists anterior tibial translation while the posterior lateral bundle is involved in rotational stability. With regards to this biomechanical function, much of the previous work on bundle-specific morphology has been carried out on the macroscale, with much less attention given to the micro-to-ultrastructural scalar levels. This is especially true of the enthesis and its microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Electrospun fibers become randomly aligned over the foil due to the disruption of the local electromagnetic field. The typical interdigitation length in soft tissue to bone interfaces varies between 0.1 to 0.5 mm and is strongly dependent on the animal species and tissue type 60,76,77 . In this study, the wave size was limited due to the manual method used to cut the foil.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Electrospun fibers become randomly aligned over the foil due to the disruption of the local electromagnetic field. The typical interdigitation length in soft tissue to bone interfaces varies between 0.1 to 0.5 mm and is strongly dependent on the animal species and tissue type 60,76,77 . In this study, the wave size was limited due to the manual method used to cut the foil.…”
Section: Resultsmentioning
confidence: 95%
“…The interface shape between the aligned and randomly aligned fibers follows the wave shape at the edge of the foil (Figure 7B cies and tissue type. 60,76,77 In this study, the wave size was limited due to the manual method used to cut the foil. To fabricate interdigitated regions that better mimic the length-scale of interfacial tissues, precise cutting dies can be designed to cut the foil into the desired shape.…”
Section: Fibrous Scaffolds With Gradients In Fiber Alignment Exhibit ...mentioning
confidence: 99%
“…However, previous studies analysing 3D histology have found clearer correlations between bone histology and musculotendinous insertions: Sanchez et al (2013) were able to determine the position of entheses in fossil vertebrates as well as the approximate orientation of the attached muscle. In addition, Cury et al (2016) and Zhao et al (2017) observed histological changes in tendon insertion zones and ligament insertion zones respectively, indicating that cortical bone holds significant information regarding muscular anatomy. Thus, if the histological level is impacted by muscle insertion, the microanatomical organisation appears rather poorly affected and a less efficient level of investigation to infer muscle structure based on skeletal elements.…”
Section: Discussionmentioning
confidence: 99%
“…22,[26][27][28]30,34 The UF and CF are bounded by the tidemark. 4,35,36 There is a transition from UF to CF, which is an intermediate gradient area. The length of the gradient in the meniscus insertion is similar to those of the ligament and tendon insertions, which is about 188 ± 56 μm in the neonatal bovid.…”
Section: Componentsmentioning
confidence: 99%